Efecto de tres niveles de lisina líquida, sobre los parámetros productivos en pollos de carne en la etapa de acabado en Yurimaguas - Hidalgo Cornejo, Luis Alberto (2018)
The present research work was carried out in the poultry shed of Mr. Henry Sifuentes Castañeda, located in Barrio Miami, in the district of Yurimaguas, province of Alto Amazonas, department of Loreto, with the objective of evaluating the effect of three levels of lysine liquid, on the productive parameters in broilers in the finishing stage in Yurimaguas. 96 broiler chickens from the Cobb line were used with an average weight of 1,176 kg, which were distributed in treatments; T0: 0.0; T1:1.0; T2:1.1 and T3:1.2 % of liquid lysine, respectively. The research was of an experimental nature and a completely randomized design (DCA) was used, consisting of 4 treatments and 4 repetitions, and the comparison of means between treatments was made using the Duncan test (5%). The results that showed the liquid lysine for the weight increase variable, T3 and T2 presented a greater increase in live weight, obtaining 2181 g and 2177 g, respectively, at the end of the trial in the seventh week, compared to T0, which obtained an increase of 2153 g and T1 with an increase in live weight of 2173 g. In feed conversion, the one that obtained the highest was T2 with 1.83. In conclusion, with 1.2% liquid lysine they cause greater weight gain (2181 g) and feed conversion efficiency (1.83), and with 1.0% liquid lysine better feed intake (191.85 g) in chickens from 21 to 42 days of age. age, likewise, better economic merit was reported in T3 with 36.42%.